The dynamics of reinforced particle migration in laser powder bed fusion of Ni-based composite - Kenny Low (Powder Technology, 2021)
The dynamics of the reinforced particles' migration remains unclear during the rapid non-equilibrium laser powder bed fusion (LPBF) process. Conducting real-time observations to obtain a comprehensive understanding of the reinforcements' movement is challenging due to the complex physical phenomena that occur during experimentation. The proposed numerical simulation in the present study incorporates a Lagrangian discrete phase model (DPM) to simulate the added submicrometre-sized TiC particles. The simulation results indicate that the migration of TiC particles was primarily induced by the combination of recoil pressure and Marangoni convection force. The TiC particles were also noted to be relatively uniformly distributed in the LPBF-fabricated Hastelloy X-1 wt% TiC composite under a 600 mm/s scanning speed. The present study offers insights into understanding the dynamics of added reinforced phases within the LPBF additive-manufacturing process to further accelerate the development of advanced metal matrix composites processed using the LPBF process.